Glosa do uchwały Naczelnego Sądu Administracyjnego z dnia 25 listopada 2013 r., I OPS 9/13 - Bulejak, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The Supreme Administrative Court resolved that after the entry into force of the Regulation of the Minister of Internal Affairs and Administration of 28 December 2005 Journal of Laws No. 266, item. 2246 proceeding in the matter of the payment of equivalent to the renovation of the occupied flat to a retired police officer shall be discontinued, despite remaining in the legal system of a decission, issued before 1 January 2006, to grant a retired officer of the Police authority the right to an equivalent for the renovation of the occupied flat. According to the court, the are two stages in the formation of right to the said benefit. The first step is to grant right to the equivalent in the form of an administrative decision, the second — to determine the yearly amount of the equivalent. The court pointed that the payment of the equivalent is a real act. For these reasons, the proceeding in the matter of the equivalent’s payment shall be discontinued as objectless. Police authorities have no legal grounds to issue a decision refusing payment of the equivalent. According to the author of this article, the above resolution should largely be accepted.
Keywords: administrative proceedings; real acts; equivalent for the renovation of the occupied flat; discontinuance of administrative proceedings; payment of equivalent for a retired police officer